The Cambrian (Guzhangian; Marjuman) kingstoniid trilobite Kingstonia Walcott, 1924 in Laurentian North America - Westrop, Stephen R.; Dengler, Alyce A.; Cuggy, Michael B. (Zootaxa, 2026)
Kingstonia Walcott, 1924 is widespread across Laurentian North America in Upper Marjuman (Guzhangian) strata. It is recorded from mixed carbonate-siliciclastic, storm-influenced facies, such as the Nolichucky Formation of Tennessee and the Sullivan Formation of Alberta, as well as shallow subtidal carbonates, including the Du Noir Formation of Wyoming. The genus ranges from the shelf interior in areas such as South Dakota to the Laurentian continental margin in Quebec and Newfoundland. This monograph focuses on the abundant material from shelf margin faunas of the Shallow Bay Formation of western Newfoundland, the Murphy Creek Formation of the Percé area, eastern Quebec, and the Grosses-Roches Formation of the southern shore of the St. Lawrence Estuary, also in Quebec. Kingstonia vagrans Lochman, 1938 occurs in all three formations, and is significant for correlation. We define a new biostratigraphic unit, the K. vagrans Fauna, which can be identified along the Laurentian continental margin in eastern Canada. Kingstonia gaspensis Rasetti, 1946 and K. phalacra sp. nov. are present in the Grosses-Roches Formation, whereas K. inflata is from the Shallow Bay Formation, and also occurs in the Nolichucky Formation of Tennessee. Kingstonia sicaria sp. nov. is from the Du Noir Formation, and a related species from Alberta is placed in open nomenclature. As part of the study, we revise K. apion Walcott, 1924 and Ucebia ara Walcott, 1924, the type species of Kingstonia and Ucebia Walcott, 1924 (considered a junior synonym of Kingstonia), respectively. We also include treatment of the types of K. inflata Resser, 1938, K. walcotti Resser, 1938, and K. rotundata Resser, 1938 from Tennessee, and K. spicata Lochman, 1940 from Missouri.